The Federal Character Principle and Its Impact on the Nigerian Public Service - IBHADE, Nkadi Francisca; MUKORO, Akpomuvire (Management Research and Behavior Journal, 2023)
Federalism is one of the best frameworks for managing a pluralistic society, and Nigeria used it to run her multiethnic state. Despite this, there appears to be division, conflict, and discord rather than cohesion, unity, and consensus. Other political strategies, including the quota system and Federal Character, were adopted as a result of the quest for national integration. The application of Federal Character, which was fully adopted in 1979, has been the subject of numerous political disputes and is currently a hot topic in political as well as administrative discourse. Thus, the purpose of this study is to investigate how the federal character principle is implemented in Nigeria's public sector. This study used the historical research design and adopted systems theory as its theoretical framework. The study's conclusion was that Nigerian federalism is far from ideal and that the Federal Character Principle, which aims to foster national loyalty, promotes unity among Nigerians, and gives all citizens a sense of belonging to the country regardless of differences in ancestry, culture, language, or religion, has not been able to achieve this goal. Among other recommendations, the study suggests that there be mechanisms in place for the effective implementation of the federal character and quota system in the Nigerian civil service, including those related to patriotism, honesty, institutionalism, and fairness. This will lessen the likelihood of conflicts between Nigeria's various ethnic groups, which are often the main reason why certain ethnic groups are excluded from civil service recruitment.